(untitled) (Research, Society and Development, 2022)
Introduction: By assuming adequate food as a social right, the Brazilian State became the bearer of the duty to respect, provide, promote and protect the Human Right to Adequate Food (HRAF) for all Brazilians, including celiacs. Therefore, it is essential that the State institute a normative apparatus compatible with the needs of the celiac population, guaranteeing the fulfillment of their rights. Objective: to assess whether the legislation in force in Brazil meets the demands of people with celiac disease. Methods: document analysis was adopted according to the methodology proposed by Pimentel. The set of documents analyzed is composed of all publications found that express the demands of celiacs, including: articles, manuals and complaint letters from representative bodies. Results: The incipience of legal instruments was observed, aggravated by the fact that a significant portion of the demands of the celiac population has not yet been covered by the current set of regulations. The legislation in force expresses the existence of specific initiatives in some Brazilian states and municipalities, which do not cover the entire national territory. This situation does not comply with the principle of universality that governs the HRAF, compromising the demand for compliance and reparation by public bodies for the celiac population. Conclusion: due to the punctual and incipient nature of the Brazilian legal apparatus, it remains predominantly the responsibility of civil society, individually or through representative associations, initiatives that guarantee the realization of the Human Right to Adequate Food for celiacs.